Federal Reserve System Rising: The Expansion of Board Veto Authority on the Eve of the Great Depression. Issue 4 (4th July 2019) - Thompson, Nicolas
ABSTRACT: Most scholars agree that restrictive Federal Reserve System (FRS) policies contributed to the depression's duration and severity. FRS policy mistakes are attributed to faulty ideas, poor leadership, and decentralised institutions. Extant scholarship treats ideas as constraints which systematically led policy-makers astray. This paper instead focuses on the dual roles ideas play in shaping institutions and uniting coalitions behind institutional projects. It traces the rise and fall of New York FRS Governor Benjamin Strong's 'great idea' that the FRS should promote international monetary stability. Declining support for New York's internationalism enabled a rural Board faction to expand its veto power from 1928 to 1930. In the critical year following the 1929 stock market crash, Board obstruction of New York FRS attempts to lower its discount and bill rates caused its investments to fall faster than the system's bond portfolio expanded, forcing outstanding system credit to contract. Beyond showing that the Board's pre-depression rise mattered, the paper speaks to broader debates about how ideas become empowered to shape policies and inform interests.